800V BIAS FOR VERY HIGH DENSITY 5KW POWER CONVERTER IN ARTIFICIAL INTELLIGENCE APPLICATIONS - Jitaru, Ionel (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
Very high power module, of 5KW operating from 800V to provide 50V with a power density of 135W/cm3 requires a bias supply to fit in a power module of a surface of less than 40cm2. That creates a major challenge because available Integrated Circuits (ICs) for such applications do not exist, and the goal is to allocate to the bias supply less than 0.8cm2 on the power module. The size of the switching devices for voltage of 1000V and above is another challenge forcing us to consider using a 650V device. The paper will present several solutions in addressing such a challenge. A layout is proposed for the chosen solution presented in this paper meeting the proposed target of 0.8mm2. The focus of this article was to offer bias solutions to a very challenging specification for 5KW power converter operating from 800V bus for Artificial Intelligence applications.